An Investigation of The Temperature Profile and Drying Kinetics of a Catfish in Biomass-Fired Kilns - Emmanuel, Ebikabowei Enemugha; Douglas, Reward Kokah; Araka, Peremelade Perez (European Journal of Applied Sciences, 2024)
This study investigated and analyzed the temperature profile and drying kinetics of biomass-fired kilns powered by gas, charcoal, and electricity. The study emphasized the importance of understanding the efficiency of energy sources in drying processes. The experimental data revealed that the drying rates varied across the compartments (Deck 1, Deck 2, and Deck 3) of the kiln when drying catfish. Notably, gas-powered kilns demonstrated faster drying times on Deck 3, while charcoal-powered kilns had different drying rates across all decks. Gas-powered kilns showed faster temperatures reaching around 250-287°C across the decks in approximately 35 minutes on average. Charcoal kilns displayed a maximum temperature of 287-298°C, with a similar drying duration. Electricity-powered kilns showcased variations in temperature profiles across the decks, with Deck 2 drying faster compared to decks 1 and 3. The results from the experiments illustrated the influence of energy sources on the drying kinetics of biomass-fired kilns. Gas, charcoal, and electricity influenced the temperature profiles and drying rates of catfish in the kiln's compartments, highlighting the need for optimizing energy sources in biomass-fired kilns. These findings have implications for enhancing drying efficiency and reducing energy consumption in industries and rural areas reliant on biomass fuel.